2016
DOI: 10.1159/000443506
|View full text |Cite
|
Sign up to set email alerts
|

The Proportion of Signet Ring Cell Component in Patients with Localized Gastric Adenocarcinoma Correlates with the Degree of Response to Pre-Operative Chemoradiation

Abstract: Background: Patients with localized gastric adenocarcinoma (LGAC), who get pre-operative therapy, have heterogeneous/unpredictable outcomes. Predictive clinical variables/biomarkers are not established. Methods: We analyzed 107 LGAC patients who had chemoradiation and surgery. LGACs were grouped for (1) presence/absence of signet ring cell histology (SRC) and (2) histologic grade: G2 or G3. %SRC was assessed (0, 1-10, 11-49, and 50-100%) and correlated with pathologic complete response (pathCR) or Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 23 publications
0
44
0
1
Order By: Relevance
“…With respect to SRCs, few studies have evaluated its predictive role for pathCR and survival in patients with esophageal AC, whereas more data are available for the predictive role of SRCs in gastric cancer . Similarly to gastric cancer, in a study reported by our group, tumors from patients with esophageal AC and SRCs had a lower pathCR rate (9% vs 26%) and more frequently had positive margins (24% vs 10%) in comparison with tumors without SRCs.…”
Section: Discussionmentioning
confidence: 84%
“…With respect to SRCs, few studies have evaluated its predictive role for pathCR and survival in patients with esophageal AC, whereas more data are available for the predictive role of SRCs in gastric cancer . Similarly to gastric cancer, in a study reported by our group, tumors from patients with esophageal AC and SRCs had a lower pathCR rate (9% vs 26%) and more frequently had positive margins (24% vs 10%) in comparison with tumors without SRCs.…”
Section: Discussionmentioning
confidence: 84%
“…Retrospective case series suggest that this gastric cancer subtype may be less sensitive to chemotherapy and CRT [IV] [96,97]. However, evidence is insufficient to support not adopting standard chemotherapy or surgical approaches for these patients.…”
Section: Signet Cell Tumoursmentioning
confidence: 99%
“…compared the concordance indices of four different TRGs (Mandard (three‐ and five‐category), Dworak/Rödel (three‐ and five‐category), Memorial Sloan Kettering Cancer Center (three‐category) and American Joint Committee on Cancer and College of American Pathologists (AJCC/CAP) (four‐category)) in a cohort of 563 patients with locally advanced rectal cancer, and concluded that the four‐category AJCC/CAP TRG was the most accurate and should be adopted as the standard . Six different TRG systems have been proposed so far for gastric cancer, including the results of a recent Delphi survey . Recently, a six‐tiered and a condensed three‐tiered chemotherapy response score (CRS) for tubo‐ovarian high‐grade serous carcinoma after neoadjuvant chemotherapy and interval debulking surgery has been proposed, and showed high reproducibility with a Kappa coefficient of 0.76 when using the condensed three‐tiered system …”
Section: Discussionmentioning
confidence: 99%